Genetic Variation in Indian Teak (Tectona grandis L.f.) Populations Assayed through Rapd Markers - Nicodemus, A.; Nagarajan, B.; Narayanan, C.; Varghese, M.; Subramanian, K. (Indian Forester, 2005)
RAPD markers were used to study genetic variation in ten Teak (Tectona grandis L.f.) populations from Western Ghats and Central regions of India. Ten oligonucleotide primers resolved 90 amplification products of which 66 (73%) were polymorphic. The total genetic diversity detected within the species (Hsp) was 0.3 Average gene diversity (H0) within different populations ranged from 0.185 to 0.261 (mean = 0.233). The Western Ghats populations had more diversity (H0 =0.227 - 0.261) compared to those from Central India (H0 =0.185-0.219). Partitioning of gel;etie diversity within and between populations showed that 78% of variation existing within populations and the rest between populations. A negative relationship was observed between latitude and within-population diversity. Nei's genetic distance between populations ranged from 0.053 to 0.264. Genetic distance. Tended to be low between populations from the same geographic region. The UPGMA dendrogram grouped the Western Ghats and Central Indian populations into two distinct clusters. Low intensity selection within populations is likely to capture a major portion of genetic diversity existing in Teak. The Western Ghats and Central Indian regions can be proposed as separate genecological zones for Teak. Future conservation strategies should aim at preserving both within and across population variation in Teak.